The Potential and Contribution of Sports Psychology to Sports Science: Literature Review - Tjung Hauw Sin; Eko Susanto (Universitas Muhammadiyah Metro, 2021)
Sports science is a complex research domain. Describe research metadata using systematic reviews and meta-analysis in sports science, then find out the potential and contribution of sports psychology studies. Today's progress of sports achievement cannot be separated from supporting factors, namely research and science in sports, which is commonly called sports science. This study aims to describe metadata using a systematic review in sports science and then find out the potential and contribution of sports psychology studies. This study refers to the PRISMA model (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The conclusion of this study is known that sports psychology research dominates one-third of the overall research found.